EXPLORING THE USE OF TECHNOLOGY FOR WEDDING CEREMONY IN DISRUPTION ERA FROM ISLAMIC PERSPECTIVE - Anggra Agastyassa Owie; Khoirina Nur Salamah (Profetik: Jurnal Komunikasi, 2023)
The Covid-19 pandemic that has occurred in Indonesia since 2019 has had an impact on educational, economic and social aspects, forcing people not to carry out activities that cause crowds such as wedding receptions. Restrictions on activities during the Covid-19 pandemic have an impact on the organization of weddings. The prohibition of crowding is the main factor that people must start honing their creativity by utilizing technology. The use of technology to answer public concerns about marriage in an Islamic perspective as a way to find out how Islam discusses the substance of marriage and how the use of technology can meet needs, especially in terms of marriage. Marriage has been discussed by Islam through the Qur'an and Hadith. This study uses a qualitative method with a library research approach. Research sources come from books, articles, and writings related to this research. The results of this study are Covid-19 does not hinder the implementation of marriages, Islam is so simple in the context of the validity of a marriage, namely the achievement of the pillars and conditions of a valid marriage, not from the form of the reception because the essence of marriage according to Islam is not how luxurious the reception is, but the terms and pillars of marriage must be fulfilled. so that activity restrictions are not an obstacle because the use of technology during the Covid-19 disruption era can be a solution.